Completed suicide risk factors among people living with HIV in Hunan Province identified through a psychological autopsy case–control study - Zhuo Yang; Xilin Chen; Xi Chen; Zhi Xie; Dan Luo (Scientific Reports)
Abstract Accumulating evidence has shown an increased risk of suicide among people living with HIV/AIDS (PLWHA). However, few studies have explored the risk factors associated with completed suicide among PLWHA. This study aimed to identify the characteristics and causes of completed suicide among PLWHA to guide future targeted suicide prevention and intervention programs. A 1:1 matched case–control psychological autopsy study was conducted among PLWHA in Hunan Province. We recruited 63 PLWHA who died by suicide from January 1, 2013, to December 31, 2019, and 63 living controls matched for age, gender, and employment. Two informants for each participant were interviewed to collect data on participants’ sociodemographic characteristics, depressive symptoms, HIV-related stress, hopelessness, and social support. The median survival time from HIV diagnosis to completed suicide was 3.9 months (IQR: 0.57–14.13). Most completed suicides occurred within six months of HIV diagnosis (71.4%), with poisoning (34.9%) and hanging (22.2%) as the primary methods. After controlling for confounding factors, we identified four risk factors of completed suicide: not receiving antiretroviral treatment (OR = 6.805; 95% CI: 1.227 to 37.738), receiving low-income subsidy (OR = 16.272; 95% CI: 3.245 to 81.598), HIV-related stress (OR = 1.332; 95% CI: 1.089 to 1.629), and hopelessness (OR = 2.910; 95% CI: 1.378 to 6.144). PLWHA are at a high risk of suicide within the first six months of HIV diagnosis, indicating an urgent need for immediate suicide screening and timely intervention. Suicide risk is affected by multiple factors, including sociodemographic, clinical, and psychological factors, indicating the need for a multifactorial approach to suicide prevention, which may involve early initiation of ART treatment and provision of economic and psychosocial support.